Hemangioma vulva pada anjing Kintamani - Sewoyo, Palagan Senopati; Teja, Putu Tessa Hariys Septianda; Wandia, I Nengah; Purbantoro, Steven Dwi (ARSHI Veterinary Letters, 2023)
Hemangioma is a common benign tumor that originates from blood and lymphatic vessels, occurring in both humans and animals. In dogs, these tumors are primarily found on the skin. This case report highlights the first reported incidence of vulvar hemangioma in a Kintamani dog. The complete blood count showed the animals had leukocytosis. Total excision of the tumor mass was performed, and postoperatively, the dog was given analgesic and antibiotic with tolfenamic acid and amoxicillin, respectively for 5 consecutive days. Topical antibiotic neomycin sulfate was also given on the surgical site. Prognosis for this case was considered good based on the nature of the tumor and its location. Based on postoperative monitoring, it can be concluded that the treatment was successful without any recurrence.